Influence of biological active substances on germination, growth and development stevia seeds (Experimental biology, 2015)
The paper presents the results on the effect of biologically active substances on the germination, growth and seeddevelopment of stevia in vitro. Revealed that these processes depend on the nature and concentration of the extracts obtained from Stevia and the time of exposure. Percentage of seed germination at 60 minute exposure was greater than 30 min exposure. High rates of germination, growth and development of the seeds was observed in treatment with Stevia extract prepared from dried leaves, water and alcohol based on the comparison with the extracts of pure stevioside and the amount of glycosides.
Keywords: Stevia seeds; germination; growth; development; extracts of stevia